Effect of Al-TiO2-C Grain Refiners on Refinement of Industrial Pure Aluminum - HAN Xiao-wei; ZHANG Rui-ying; WANG Peng (Cailiao gongcheng, 2017)
The Al-TiO2-C grain refiners were synthesized by the in-situ exothermic dispersion method by using TiO2,C and Al powders as raw materials. The microstructure of Al-TiO2-C refiners with different C/TiO2 was investigated by SEM, XRD and EDS. Grain refining test was carried out on industrial pure aluminum. The results show that Al-TiO2-C refiners are composed of Al3Ti,TiC and Al2O3. When the mole ratio of C to TiO2 is between 1:25 and 1:20, the amount of Al2O3 is moderate and its distribution is relatively dispersive. An excellent grain refining performance is obtained when adding 0.2% (mass fraction) Al-TiO2-C refiner with C/TiO2 is 1:20, the average grain size is about 142μm and there is no refining recession when holding 1h.